Laser Bioprinting of Cells Using UV and Visible Wavelengths: A Comparative DNA Damage Study - Panagiotis Karakaidos; Christina Kryou; Nikiana Simigdala; Apostolos Klinakis; Ioanna Zergioti (Bioengineering, 2022)
Laser-based techniques for printing cells onto different substrates with high precision and resolution present unique opportunities for contributing to a wide range of biomedical applications, including tissue engineering. In this study, laser-induced forward transfer (LIFT) printing was employed to rapidly and accurately deposit patterns of cancer cells in a non-contact manner, using two different wavelengths, 532 and 355 nm. To evaluate the effect of LIFT on the printed cells, their growth and DNA damage profiles were assessed and evaluated quantitatively over several days. The damaging effect of LIFT-printing was thoroughly investigated, for the first time at a single cell level, by counting individual double strand breaks (DSB). Overall, we found that LIFT was able to safely print patterns of breast cancer cells with high viability with little or no heat or shear damage to the cells, as indicated by unperturbed growth and negligible gross DNA damage.